Phytochemical study of stem bark from Alstonia spathulata Bl. (Apocynaceae) - Tee Chuan Thing, Lee Yean Shan, Tan Siow Ping, Awang Khalijah, Nafiah Mohd Azlan, Ahmad Kartini (N/A, 2014)
Phytochemical study of stem bark from Alstonia spathulata Bl. (Apocynaceae) by Tee Chuan Thing, Lee Yean Shan, Tan Siow Ping, Awang Khalijah, Nafiah Mohd Azlan, Ahmad Kartini,